Desenvolvimento e validação de metodologia analítica para quantificação de Iangambina e seu epímero em extratos de Ocotea duckei (Lauraceae) - Leal, Sandro de Sousa (2012)
Yangambin, a furofuran lignan isolated from Ocotea duckei Vattimo (Lauraceae) has important pharmacological activities, such as selective antagonist of platelet activating factor (PAF), cardiovascular protective effects, CNS depressant, and others. Besides, it is presented as a phytochemical marker of the specie and a promising substance for a herbal drug development. Thus, this study aimed at the development and validation of an analytical method on HPLC-DAD for simultaneous quantitative determination of yangambin and its epimer, epi-yangambin, in extracts and fractions of Ocotea duckei. For method development, a synthetic approach was made in order to obtain the lignans with high purity. The synthetic route includes a biotransformation process with coconut water peroxidase for a stereoseletive synthesis of yangambin. The chromatographic conditions for the study were: reverse phase column C-18 (250 x 4,6 mm x 5 μm), mobile phase was a mixture of water and acetonitrile (50:50) at a flow rate of 1,0 mL/min, detection at a wavelength of 215 nm. Lignans were isolated from crude ethanolic extract of the plant (leaves and stem bark) through a lignoids isolation procedure. Epimers were separated by semi-preparative HPLC-DAD to yield compounds free from impurities, being characterized by spectroscopic methods (1H and 13C NMR), infrared (IR), mass spectrometry (MS), optical rotation, circular dichroism, and thermal analysis. Validation of analytical method was performed in accordance with Resolution nº 899/2003, from ANVISA, proving to be: selective for the two epimers, linear at the concentration range of 1,0 60,0 μg/mL, precise (CV ≤ 5% ), accurate (99-101%) and robust. Application of the validated analytical method in a quantitative study allowed to determine that each 1,0g of crude ethanolic extract from stem bark and leaves presents 58,07 mg of yangambin and 88,94 mg of epi-yangambin. In total lignoids fraction, each 1,0g has 188,75 mg of yangambin and 250,02 mg of epi-yangambin.